Novel circuits involved in Drosophila melanogaster virgin female sexual behaviours - Carvalho, Eliane Ochôa Arez de Carvalho (2021)
"Courtship is a set of species-specific behaviours that provide a way by which male and female communicate, allowing the display of fitness of one sex (male) to the other (female) and leading to mating. This innate behaviour present in all animals, is crucial for reproduction and species survival. In Drosophila melanogaster, courtship consists of a series of stereotyped actions performed by the male towards the female, while she evaluates him by the sensory cues presented to her. At the end, the male may decide to attempt copulation, but it is the female who will decide whether or not to mate. (...)"